Performance Analysis on Security Association in High Speed ATM Networks - Cheong, W. H.; Ling, T. C.; Hj. Yaacob, Mashkuri; Phang, K. K. (Malaysian Journal of Computer Science, 2003)
The ATM Forum has released an ATM Security Specification that contains the requirements and specifications of security support services. The ATM Security Specification suggests placing all the security features in the user plane, control plane, management plane, ATM adaptation layer and ATM layer of ATM network architecture. Implementing security features in these planes and network layers will introduce extra overhead on data transmission. The key reason is that security options, algorithms, and key lengths have to be negotiated via Security Message Exchange (SME) before any security services can be provided. This paper aims to carry out performance analysis to determine the cell throughput and SME setup time for different sets of security association topologies. For this purpose, security support services are implemented and integrated with the NIST ATM/HFC Network Simulator. From this performance testing, the specific security association topology that provides the best performance could be selected.